Chronic Osteomyelitis of Wrist Joint in An Immunocompromised Host - Amanda P Utari; Dina Oktavia; Sumaryono Sumaryono; Bambang Setyohadi (Indonesian Journal of Rheumatology, 2014)
Osteomyelitis is heterogenous in its pathophysiology, clinical presentation, and management. Osteomyelitis is generally categorized as acute or chronic based on histopathologic findings, rather than duration of the infection. Necrotic bone ispresent in chronic osteo-myelitis, and symptoms may not occur until six weeks after the onset of infection.1 Epidemiology of chronic osteomyelitis is less well characterized compared with acute osteomyelitis. Adult osteomyelitis most commonly arisesfrom open fractures, diabetic foot infections, or the surgical treatment of closed injuries. HematogenousÂ  osteomyelitis accounts for approximately 20% of cases of osteomyelitis in adults. It is more common in males regardless of age. Although rare in adults,it most frequently involves the vertebral bodies.2 S.aureus is the most common isolate in all types of bone infection and is implicated in 50-70% of cases of chronic osteomyelitis.3